МАКТАБГАЧА ТАЪЛИМ МУАССАСАЛАРИ ПЕДАГОГ ХОДИМЛАРИ ВА РАҲБАРЛАРИ МАЛАКАСИГА ҚЎЙИЛГАН ТАЛАБЛАР - Ибрагимова, Г.Н. (SCIENCE and SOCIETY, 2018)
The article is devoted to the issues of preschool education development of the quality of preschool education, improving preschool education based on new social order and requirements on preschool education put by the state, and reforms in the sphere of preschool education.
Keywords: preschool education; education process; modernization; pedagogical management; leader; pedagogical staff